2019
DOI: 10.1111/jir.12707
|View full text |Cite
|
Sign up to set email alerts
|

A profile of mental health and behaviour in Prader–Willi syndrome

Abstract: BackgroundPrader–Willi syndrome (PWS) is a neurogenetic syndrome with an associated behavioural phenotype and a high incidence of behaviours of concern and psychiatric co‐morbidity. These associated behaviours and co‐morbidities are not well addressed by existing interventions, and they impact significantly on affected individuals and their caregivers.MethodsWe undertook a national survey of the needs of individuals with PWS and their families in Ireland. In this paper, we report on the parent/caregiver‐report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 39 publications
6
31
2
Order By: Relevance
“…In line with the previous reports [ 12 , 27 29 ], high rates of behavioral and psychiatric comorbidity were reported in this sample (Table 3 ). As in general population research, in this collection of individuals with PWS, those with a reported history of SI were more likely to have depression, anxiety, bipolar disorder, or psychosis and more likely to be receiving therapeutic or pharmacologic mental health treatments.…”
Section: Discussionsupporting
confidence: 93%
“…In line with the previous reports [ 12 , 27 29 ], high rates of behavioral and psychiatric comorbidity were reported in this sample (Table 3 ). As in general population research, in this collection of individuals with PWS, those with a reported history of SI were more likely to have depression, anxiety, bipolar disorder, or psychosis and more likely to be receiving therapeutic or pharmacologic mental health treatments.…”
Section: Discussionsupporting
confidence: 93%
“…Some studies in PWS did not appear to capture the challenge of anxiety in the PWS population [37,38]. Other studies have, however, found moderate to high levels of anxiety in PWS samples [3,7,39]. Different approaches in assessing anxiety were utilized in these studies that may explain the discrepancies between results.…”
Section: Plos Onementioning
confidence: 96%
“…Individuals with PWS present with central hypotonia and feeding problems in early infancy, followed during childhood and adulthood by intellectual and learning disabilities, maladaptive behaviors, hypogonadism and incomplete sexual development, short stature due to growth hormone deficiency and severe hyperphagia, which is a hallmark symptom of the syndrome. Emotional and behavioral challenges are prominent in PWS and include anxiety, repetitive behaviors, temper outbursts, and oppositional behavior [2][3][4][5][6][7]. As individuals with PWS reach adulthood, they are at high risk for developing psychiatric illness, including psychosis and major depression [8].…”
Section: Introductionmentioning
confidence: 99%
“…Distinct behavioural traits are common, among them stubbornness, compulsions, temper outbursts and skin-picking (Whittington and Holland 2018). Repetitive questioning and difficulties in dealing with change are also characteristic and were described by caregivers as resulting in frequent misconduct (Feighan et al 2020). Furthermore, individuals with PWS seem to have a higher susceptibility to psychiatric disorders, mainly obsessive compulsive behaviours, depression, autism spectrum disorders and psychosis (Soni et al 2007;Soni et al 2008).…”
Section: Introductionmentioning
confidence: 99%